Putative Blood Biomarkers on Tropical Resilience in Philippine Native and Crossbred Heifers - Pandangan, E. M. I.; Dominguez, J. M. D.; Turaja, K. I B.; Guadayo, G. F.; Sumaya, N. H. N.; Tabugo, S. R. M.; Del Barrio, A. N.; Kim, K. S.; Moneva, C. S. O. (Tropical Animal Science Journal, 2026)
Hematological values are essential in understanding the health of an animal. Interpretation of these values must consequently be clinically accurate. These values are also putative biomarkers for resiliency under tropical conditions. In this study, blood profiles of Panay Native (PN) and crossbred Holstein x Jersey (HxJ) heifer cattle were compared to identify biomarkers of tropical resilience. Blood samples from 58 heifers were analyzed using General Linear Models and multivariate techniques. Results demonstrated that temperate-derived Reference Intervals frequently misclassified healthy animals. The Panay cattle exhibited a superior erythropoietic phenotype (significantly higher RBC, HGB, PCV, p